Monocyte-Dependent Suppression of T-Cell Function in Postoperative Patients and Abdominal Sepsis. Issue 6 (December 2017) - Albertsmeier, Markus; Prix, Niclas J.; Winter, Hauke; Bazhin, Alexandr; Werner, Jens; Angele, Martin K.
ABSTRACT: Introduction: Surgical trauma causes inflammation and postoperative immunosuppression. Previous studies have shown a T-cell-dependent suppression of MHC II expression and other functions of antigen-presenting cells. The aim of this study was to determine which immune cell initiates postoperative immunosuppression and consecutive sepsis. Methods: We separated T-cells and monocytes in human abdominal surgery (n = 11) patients preoperatively as well as 24 h postoperatively and in patients who developed postoperative sepsis (n = 6). We analyzed their surface markers and then coincubated these cells with naïve preoperative cells of the other cell type, respectively. Cytokine secretion from naïve cells was measured by a multiplex immunoassay, serving as a bioassay for the function of the stimulating postoperative cell. Results: Surface marker analysis showed a postoperative suppression of CD3 + cells and the activation marker CD28 ( P = 0.02), which was further reduced in septic patients. FACS analysis revealed a significant increase in CD14 + monocytes ( P = 0.02) and CD14 + CD86 +, CD14 + HLA-DR + subpopulations 2 h postoperatively. In sepsis patients, HLA-DR expression was reduced compared with postoperative levels ( P < 0.01). After coincubation with postoperative T-cells, secretion of IL-6 ( P < 0.01) and IL-10 ( P < 0.01) from naïve monocytes was increased, whereas T-cells from sepsis patients resulted in suppressed cytokine secretion. After coincubation with postoperative monocytes, secretion of IFN-gamma ( P < 0.01) and IL-10 ( P < 0.01) from naïve T-cells was significantly diminished, whereas monocytes from septic patients triggered only insignificant IL-10 secretion from naïve and septic T-cells. Conclusions: Our results show that in the early postoperative period, T-cells are suppressed but able to trigger the release of cytokines from monocytes, whereas activated monocytes seem to induce T-cell suppression. In sepsis patients, a global suppression of both cell types in terms of absolute numbers and function seems to occur.